Analysis of the Effectiveness of Quick Response Code Indonesian Standard (QRIS) As A Digital Payment Tool Among Students - Gina Puspita; Aen Fariah (Politeknik Siber Cerdika Internasional, 2026)
The rapid expansion of digital payment systems has accelerated the adoption of the Quick Response Code Indonesian Standard (QRIS) across various sectors, including higher education. Although QRIS has become a widely used cashless payment method in Indonesia, empirical evidence regarding its effectiveness among university students remains limited. This study aims to analyze the effectiveness of QRIS as a digital payment instrument among students and identify the factors influencing its use. A descriptive quantitative approach was employed by distributing online questionnaires to 90 active students selected through purposive sampling, representing 30% of the total population of 300 students using mobile banking or digital wallets. Effectiveness was measured using four indicators: perceived ease of use, perceived usefulness, time efficiency, and transaction security. The research instrument was tested for validity using Pearson product-moment correlation and reliability using Cronbach's Alpha, with all items meeting the accepted validity criteria and demonstrating satisfactory reliability (Cronbach's Alpha > 0.70). Descriptive statistical analysis revealed an average effectiveness index of 84.5%, indicating that respondents generally perceived QRIS as highly effective based on the predetermined assessment criteria. The primary factors supporting positive perceptions were transaction speed, convenience, and the elimination of the need for physical cash or change. However, internet connectivity instability and mobile device limitations, particularly low battery conditions, remained the main obstacles affecting transaction continuity. These findings contribute to the literature on digital payment adoption by providing empirical evidence on QRIS effectiveness among university students and offering practical insights for improving the quality and reliability of digital payment services in higher education environments.